Assessment of Spanish hospitals involved in the Quality Oncology Practice Initiative program. Issue 28 (1st October 2022) - Garcia-Foncillas, Jesus; Lopez, Rafael; Camps, Carlos; Guillem, Vicente; Alonso, Jose Luis; Carrato, Alfredo; Martín, Nicole; Paz-Ares, Luis G.; Provencio, Mariano; Esteban, Emilio; Ayala, Francisco; Pérez-Segura, Pedro; et al.
Abstract : 305 Background: Measuring and tracking quality of care is highly relevant in today's healthcare. The Quality Oncology Practice Initiative (QOPI) program is a referral for evaluating oncology practices worldwide. The ECO Foundation (Excellence and Quality in Oncology), a collaboration of oncology experts from the major Spanish hospitals involved in cancer treatment, reached an agreement with ASCO (American Society of Clinical Oncology) to include Spanish hospitals in its QOPI program. Methods: We analyzed the scores of the QOPI rounds from 14 Spanish hospitals, which submitted their charts from 2016 to 2021, and the measures obtained from 2018 to 2021, regarding the core/symptom, breast, colorectal (CRC) and NSCLC modules, in comparison with the QOPI aggregate measures. Results: Since 2016, 14 Spanish hospitals have participated in the QOPI program, achieving the certification 12 of them, and 3 are in process. Along the years, they have obtained a score over 85%, being 87, 41% the worse in 2021, and 92, 80% the best in 2020. We also analyzed the outstanding measures from 2018 onwards. The highest scores in Spanish hospitals were for information of infertility risks and chemotherapy intent prior to prescription, and documented plan for oral chemotherapy. However, measures regarding pain addressed, appropriate antiemetic therapy for high- and moderate-emetic-risk antineoplastic agents and action taken to address problems with emotional well-being by the second office visit, were among the lowest scored measures. When we focused in breast and NSCLC modules, Spanish hospitals didn´t show negative values, highlighting in the administration of Tamoxifen or AI within 1 year of diagnosis by patients with AJCC Stage IA (T1c) and IB - III ER or PR positive and in the status documentation for patients with initial AJCC Stage IV or distant metastatic NSCLC. In CRC module, Spanish hospitals showed lower scores in colonoscopy before or within 6 months of curative colorectal resection or completion of primary adjuvant chemotherapy. Conclusions: This study evaluates QOPI scores in Spain, showing that repeated participation enhances quality of care, although there is room for improvement. ECO Foundation will continue supporting Spanish practices to increase their participation aiming of improve oncology care in Spain.